2009
DOI: 10.1002/pros.21015
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 deiodinase activity and generation of triiodothyronine (T3) in prostate of sexually active rats

Abstract: The increased local generation of T(3) in prostate might be related to: (1) the differentiation/maturation that occurs at puberty and (2) the energy expenditure associated with maintaining the secretory activity of the glandular epithelium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…[18,19,47,48], and, second, as a modulating factor to maintain the integrity and differentiation of prostate epithelium. First, T 3 directly stimulates glycosidase activity in normal prostate [14,15]; second, T 3 and androgens have synergistic effects on proliferation and expression of prostate-specific antigen in the differentiated tumoral cell line LNCaP [49]; and, third, there is a decrease of D1 activity (unpublished data) and a loss of responsiveness to T3 in the dedifferentiated prostate cancer cell line DU145 [50].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[18,19,47,48], and, second, as a modulating factor to maintain the integrity and differentiation of prostate epithelium. First, T 3 directly stimulates glycosidase activity in normal prostate [14,15]; second, T 3 and androgens have synergistic effects on proliferation and expression of prostate-specific antigen in the differentiated tumoral cell line LNCaP [49]; and, third, there is a decrease of D1 activity (unpublished data) and a loss of responsiveness to T3 in the dedifferentiated prostate cancer cell line DU145 [50].…”
Section: Discussionmentioning
confidence: 99%
“…In both tissues, D1 activity is present at the onset of puberty and sexual maturity [17,18]. In non-sexually active males, we have found that the prostate T 3 concentration decreases with age, but long-term (1 and 5 months) continuation of sexual activity prevents the age-related decline [19]. It has been demonstrated that prostate D1 activity is under a complex endocrine control, mediated by inhibitory (androgens) and stimulatory (estrogens, prolactin, hyperthyroidism) factors [17].…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Later, it was shown that DIO1 enzymatic activity is present in the prostate of pubescent rats and in 3-month-old young-adult rats. In contrast, this activity is practically undetectable in the postnatal period and in rats older than five months of age ( 11 , 12 ). Sexual behavior is the central stimulus for prostate function, and a study in breeding rats showed that sexual activity prevents the decline of DIO1 activity associated with aging ( 12 ).…”
Section: Transport Uptake and Bioavailability Of Thyroid Hormones In ...mentioning
confidence: 96%
“…In addition, DIO1 activity is under endocrine control; it is stimulated by T4, estrogens, and prolactin (PRL) and is negatively regulated by androgens ( 11 ). An association between enzymatic activity and prostatic T3 levels was observed during different physiological challenges ( 12 , 13 ). Nevertheless, the contribution of DIO1 to T3 generation has been questioned in recent years, and instead, it has been suggested that this enzyme contributes to iodine recycling ( 1 , 2 ).…”
Section: Transport Uptake and Bioavailability Of Thyroid Hormones In ...mentioning
confidence: 97%